2019
DOI: 10.7150/thno.28376
|View full text |Cite
|
Sign up to set email alerts
|

Highly-Soluble Cyanine J-aggregates Entrapped by Liposomes for In Vivo Optical Imaging around 930 nm

Abstract: Near infrared (NIR) dyes are useful for in vivo optical imaging. Liposomes have been used extensively for delivery of diverse cargos, including hydrophilic cargos which are passively loaded in the aqueous core. However, most currently available NIR dyes are only slightly soluble in water, making passive entrapment in liposomes challenging for achieving high optical contrast. Methods : We modified a commercially-available NIR dye (IR-820) via one-step Suzuki coupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 52 publications
0
23
1
Order By: Relevance
“…There are several reports on J-aggregation of short-chained cyanine dye within lipid bilayers, but these formulations were spectroscopically active only in the visible light regions [40,42]. Miranda et al recently reported the first liposomal formulation of J-aggregate, based on a dicarboxylphenyl modified IR-820 dye (DCP-Cy), intended for NIR spleen imaging [43]. J-aggregation of DCP-Cy relied on salt-induced J-aggregation, and a basic environment (pH 10 -11), resulting in an absorbance peak at 934 nm.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports on J-aggregation of short-chained cyanine dye within lipid bilayers, but these formulations were spectroscopically active only in the visible light regions [40,42]. Miranda et al recently reported the first liposomal formulation of J-aggregate, based on a dicarboxylphenyl modified IR-820 dye (DCP-Cy), intended for NIR spleen imaging [43]. J-aggregation of DCP-Cy relied on salt-induced J-aggregation, and a basic environment (pH 10 -11), resulting in an absorbance peak at 934 nm.…”
Section: Discussionmentioning
confidence: 99%
“…For example, indocyanine green (ICG), an FDA-approved clinical NIR imaging agent, has been reported to bind with serum proteins resulting in the switching between aggregated and monomeric forms which consequently change the spectral features [ 62 ]. To improve the stability and circulation of dye aggregates in vivo, synthetic scaffolds, such as polymers, inorganic nanoparticles, and lipid vesicles, have been used to co-assemble [ 63 ] or encapsulate [ 64 ] the densely packed dye aggregates. Sletten et al have reported the use of hollow mesoporous silica nanoparticles to trap the J-aggregates formed by the NIR chromophore IR-140 [ 65 ], where the dye aggregates were encapsulated by nanoparticles which showed enhanced stability and have been used to achieve efficient in vivo imaging (Fig.…”
Section: Utilization Of Dye Aggregates For Biomedical Applicationsmentioning
confidence: 99%
“…Many OA/fluorescence NPs are targeted toward integrin α(v)β(3) which is overexpressed in endothelial cells in the glioblastoma mouse model. Near-infrared (NIR) I range NPs in glioblastoma imaging include quantum dots ( Zhao et al, 2020 ), gold NPs ( Lu et al, 2011 ; Kircher et al, 2012 ; Lozano et al, 2012 ; Shang et al, 2017 ), copper/iron-based NPs ( Wu M. et al, 2018 ; Zhou et al, 2018 ; Zhang et al, 2019b ), carbon nanorods ( Pramanik et al, 2009 ; Qian et al, 2018 ), MoS 2 nanosheets ( Chen et al, 2016 ; Guo et al, 2017 ), semiconducting polymeric NPs ( Yang et al, 2019 ), nanodot–chlorotoxin conjugates ( Wu et al, 2011 ), polymer-encapsulated organic NPs ( Li and Liu, 2014 ), ICG-holo-transferrin NPs ( Zhu et al, 2017 ), and liposomes ( Miranda et al, 2019 ). The circulating dyes and NPs accumulate in brain tumors due to a disruption of the blood–brain barrier ( Kircher et al, 2012 ; Burton et al, 2013 ; Neuschmelting et al, 2018 ) or enhanced permeability and retention effect ( Li et al, 2018b ).…”
Section: Hybrid Contrast Agents For Multimodal Oa Brain Imagingmentioning
confidence: 99%